Fakta & data Yahudi di Indonesia dulu dan kini - Saidi, Ridwan, 1942-; Ridyasmara, Rizki, 1971-; Saidi, Ridwan, 1942- (Jakarta : KHALIFA, 2006)
History of Jewish activities in Indonesia since Dutch colonial until now.
Rev. ed. of : Fakta & data Yahudi di Indonesia dan refleksi perdamaian PLO-Israel.
Keywords: Jews -- Indonesia -- History